Innovation and Archive Management in Improving the Performance of the Probolinggo City DPRD - Dwi Putranto Riau; Ridho Harta; Ricky Patra Hakim (Indonesian Association for Public Administration (IAPA), 2021)
The current condition of the COVID-19 pandemic has made government offices implement work from home this has resulted in a large number of official archives, , especially the letter of responsibility (SPJ) for official travel and the letters that come in every day make the archives pile up and also the archives that do not fit to accommodate the archives, the implementation of activities that are hampered because the disposition letter of the leadership has not been dropped and the use of Simaya's correspondence application by The leadership of the DPRD and the DPRD Secretariat who have not been integrated into accelerating the disposition of program implementation policies. This makes SKPD leaders need a strategy to reduce the archives that keep coming and integrate programs and activities. One of the strategies is to digitize archives. This study uses a qualitative method by conducting interviews with related actors, namely archivist functional officers and structural officials as well as secondary data staff. The results of the study show that innovation and archive management, one of which is archive digitization, can reduce the place to accommodate archives, work faster in data access, and can support improving the performance of the Probolinggo City DPRD.